Esculetin Combats Multidrug-Resistant Salmonella Infection and Ameliorates Intestinal Dysfunction via the Nrf2 Pathway - Wenjiao Xu; Wenjun Ding; Liyan Jia; Kui Zhu; Qingfeng Luo (MDPI AG, 2024)
The increasing incidence of multidrug-resistant (MDR) Salmonella enterica serovar Typhimurium (S. Tm), known for causing invasive enteric infections, presents a significant public health challenge. Given the diminishing efficacy of existing antibiotics, it is imperative to explore novel alternatives for the treatment of MDR S. Tm infections. Here, we identified esculetin (EST), a natural coumarin abundant in dietary foods and herbs, as a compound exhibiting broad-spectrum antibacterial properties against a range of MDR bacteria. Our findings demonstrate that EST effectively inhibited the proliferation and expansion of MDR S. Tm in both in vitro experiments and animal models. Specifically, EST significantly downregulated the type 3 secretion system-1 (T3SS-1) virulence expression of MDR S. Tm, thereby preventing its invasion into intestinal epithelial cells. In S. Tm-infected mice, we observed cecal injury characterized by the upregulation of inflammatory cytokines, a reduction in goblet cell numbers, a decreased expression of tight junction proteins, and microbial dysbiosis. Conversely, EST treatment ameliorated these pathological changes induced by S. Tm infection and reduced oxidative stress by activating the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway, thereby improving intestinal barrier function. These results suggest that dietary coumarins or a targeted plant-based diet may offer a promising strategy to counteract MDR bacteria-induced enteric diseases.